Estimasi Biaya Perangkat Lunak Menggunakan Metode Function Point (Studi Kasus: CV Aptikma Indonesia) - Mohammad Rizqi Zamzami Alnobeta; Mochamad Chandra Saputra; Admaja Dwi Herlambang (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
When the process of developing software with different size and functional become so fast, it makes the problem in cost estimation and effort estimation higher. Research explains the scope of Software A and Software B on CV Aptikma Indonesia using the approach of the Work Breakdown Structure as well as scheduling using Gantt Chart and the results of the estimated costs of using the method of Function Point. The mathematical calculation on software A, using the method of Function Point produce the effort a number of 56 for five months with a total cost amounting to Rp 610.000.000, 00. While the software B produce an estimated effort a number of nine people for six months with a total cost amounting to Rp 59.350.000, 00. Analysis of the comparison between the method of Function Point and Guesstimate on software A and software B can be the subject of consideration CV Aptikma Indonesia in resolving the problem.